Protective effects of melatonin against 2,2-dichlorovinyl dimethyl phosphate-induced reproductive toxicity in adult male Wistar rats - Ajani, Olumide Samuel; OMOYENI, Edamisan John; Akinniyi, Olumide Odunayo (Archives of Veterinary Science, 2025)
Organophosphorus compounds, particularly 2,2-dichlorovinyl dimethyl phosphate (DDVP), are widely used pesticides that can cause reproductive toxicity in animals. While various antioxidants have been studied to mitigate DDVP toxicity, the potential of melatonin (MLT) in preventing DDVP-induced reproductive toxicity remains underexplored. This study evaluated the fertility of melatonin-protected adult Wistar rats exposed to DDVP. Sixty adult male Wistar rats were divided into four groups: control (0.2ml corn oil orally), MLT-treated (10 mg/kg intraperitoneally), DDVP-treated (1.6 mg/kg orally), and DDVP+MLT-treated (1.6 mg/kg DDVP orally + 10 mg/kg MLT intraperitoneally). The 45-day treatment regimen was followed by assessments at 24 h, and 14 and 45 days post-treatment. Blood samples were analyzed for hormone levels using ELISA. Sperm characteristics were evaluated using standard techniques, including Wells and Awa stains for morphology and Eosin-Nigrosin stain for viability. Results showed that chronic DDVP exposure significantly decreased testosterone and LH levels (p < 0.05), reduced sperm motility and viability (P < 0.05), and increased morphologically abnormal spermatozoa (p < 0.05) at 45 days post-treatment. Sperm abnormalities were primarily observed in the tails. Co-administration of MLT with DDVP significantly improved these parameters (p < 0.05), demonstrating its protective effects against DDVP-induced spermatotoxicity. No significant changes were observed in sperm morphometry or FSH and estradiol levels across all groups (p>0.05). Melatonin protects against DDVP-induced male reproductive toxicity in rats by improving hormonal profiles, sperm parameters, and morphology. The data suggests the potential of MLT as a protective agent against organophosphate-induced dysfunction. Further research is recommended to investigate melatonin's protective mechanisms and long-term effects.